Skill-learning by observation-training with patients after traumatic brain injury - Avraham, Einat; Sacher, Yaron; Maaravi-Hesseg, Rinatia; Karni, Avi; Doron, Ravid (Frontiers in Human Neuroscience, 2022)
Traumatic brain injury (TBI) is a major cause of death and disability in western society, and may often result in decrease of functional and neuropsychological abnormality. Memory impairment is one of the most significant cognitive implications after TBI. In the current study we investigate procedural memory acquisition by observational training with TBI patients. It was previously found that while practicing a new motor skill, patients engage in all three phases of skill learning (fast acquisition, between-session consolidation gains, and long-term retention), though their pattern of learning was atypical compared to healthy participants. A different set of studies showed that training by observing a motor task, generally constituted effective acquisition and consolidation of procedural knowledge with healthy participants. The aim of our study was to (i) initially evaluate the potential for TBI patients to benefit from action observation. (ii) Examine the possibility of improvement in performance between different time-lines during the study. (iii) Investigate the link between performance and common measures of injury (such as severity of injury, functional and cognitive measures). Methods: Patients hospitalized after moderate to severe TBI, were trained by observation for the FOS (finger opposition sequence) motor task. They were then tested for the observation-trained sequence (A) and a similar control sequence (B), in two different timelines (24 hours post training and 2-week later). Results revealed (i) a significant differences in performance between the trained (A) and untrained (B) sequences, in favor of the trained sequence A. (ii) An increase in performance for both sequence A and B towards the second (retention) session. (iii) The advantage for sequence A was stable and preserved also in the second session. (iv) Participants with relatively lower-moderate Functional Independent Measure (FIM) scores gained more from observational-procedural learning, compared to patients with higher functional abilities. Conclusions: Overall, these findings support the notion that TBI patients may achieve procedural memory consolidation and retention by observational learning. Moreover, different functional traits may predict the outcomes of observational-training for patients. These finding may have significant practical implications in the future, regarding skill acquisition methods with TBI patients.